Threats to Education: Research on the Use of Chatgpt - Utzinger Morales; Schittny Joanan; Hirsiger Julia (Yayasan Adra Karima Hubbi, 2023)
Background. The presence of ChatGPT which is used continuously will make students lose their motivation to study. If students continue to use ChatGPT, this will become a problem for the students themselves. For not doing the job according to his ability. So students will not get value with what they get. Purpose. this is done to find out the threat to the world of education: research on the use of ChatGPT. Method. using quantitative methods, data obtained through interviews and distributing questionnaires online using the Google form. Results. resultThis explains that the danger of continuous use of ChatGPT will be a bad influence on students. Where the enthusiasm for student learning decreases, when they get assignments from their lecturers. These students will look for answers in ChatGPT and they will not use existing sources such as books, articles and journals. Conclusion. limitationsThis research is only conducted at a university in an Arab country